Acoustic Emission-Based Method for IFSS Characterization in Single-Fiber Fragmentation Tests - Felipe Romero; Franco Méndez; Javiera González; Víctor Tuninetti; Carlos Medina; Meylí Valin; José Valin; Alexis Salas; Cristián Vicuña (Applied Sciences)
Carbon fiber-reinforced polymers (CFRP) are widely used composite materials in structural applications, where their mechanical performance is significantly influenced by interfacial shear strength (IFSS). The single fiber fragmentation test (SFFT) is a common technique for characterizing IFSS, but its reliance on optical microscopy makes it time-consuming and impractical for opaque matrices. This study presents an alternative methodology based on acoustic emission (AE) analysis, enabling the estimation of fragment lengths through statistical modeling. The AE technique captures the energy released during fiber fragmentation, represented as AE bursts, whose accurate detection is crucial. A signal-processing approach based on progressive simplification enhances burst detection. To refine the estimation of fragment lengths, a gamma distribution is fitted to experimental data, accounting for observed asymmetry in optical measurements. Results indicate that this approach achieves an IFSS determination error of 14.16% at a 95% confidence level. This study demonstrates the feasibility of using AE for IFSS characterization in SFFT and contributes to future research on AE applications in composite materials.